Tinjauan Yuridis terhadap Syarat Formil dan Materil UU No 37 Tahun 2004 terhadap Perkara Kepailitan pada Putusan Nomor 09/Pdt.Sus-Pkpu/2015/Pn.Niaga Medan - Dinda Agita Sari; Elvi Zahara (Universitas Medan Area, 2018)
Juridical Issues Against Formality and Material Requirements From Uu No. 37 of 2004 Against Bankruptcy Cases of Decision Number 09 / Pdt.Sus-Pkpu / 2015 / Pn.Niaga MedanThis thesis is basically about what are the formal requirements and material requirements of Law No. 37 of 2004 concerning bankruptcy cases and relating them to the bankruptcy case of PT. Bumi Minang Padang Plaza Hotel. The proposed discussion is the regulation of bankruptcy law in Indonesia, with debt restructuring and the postponement of bankruptcy debt payment obligations, as well as the legal consequences of the bankruptcy decision of PT. Bumi Minang Padang Plaza Hotel. To discuss these problems, the primary legal material research is carried out, namely the material that is binding because it is issued by the Government, among others: statutory regulations, court decisions and treaties, the second is secondary legal material, namely materials which discuss primary material, between Other: books, articles, research reports, as well as various other scientific papers and all three tertiary legal materials, namely materials that support primary and secondary materials, among others: internet and others and conduct field research in the Medan Commercial Court